The evolutionary history of IGKC in mammals reveals ancient duplications and remarkable divergence in lagomorphs - Pinheiro, Ana; Borges, J. Ricardo; Marques, João Pedro; Esteves, Pedro José (Frontiers in Immunology, 2025)
BackgroundThe Immunoglobulin Kappa Constant (IGKC) gene encodes the constant region of the immunoglobulin kappa light chain, a crucial component of antibodies. Despite its important biological role, the genetic information for this gene remains scarce, with data for only 16 mammal species (as of July 2025) fully characterized in the International ImMunoGeneTics information system (IMGT) database.ResultsUsing genomic sequences from NCBI and Ensembl, we expanded this to 124 IGKC sequences across 104 mammals, including two monotremes, eight marsupials, and 94 placentals. We uncovered unusual evolutionary dynamics in lagomorphs, showing independent IGKC duplications in Ochotonidae and Leporidae, giving rise to rabbit IGKC1 and IGKC2. No conserved glycosylation sites were found, but 26 sequences from 14 species carried potentially N-glycosylated sites, including two new sites in lagomorphs. Selection analyses revealed pervasive purifying selection interspersed with codons under positive selection, while aBSREL identified episodic diversifying selection in several lineages.ConclusionsOur study represents a significant contribution to the knowledge of the IGKC gene, substantially expanding on information available in IMGT. It highlights complex evolutionary trajectories, especially in lagomorphs. The presence of N-glycosylated sites suggests potential effects on antigen binding, stability, or half-life. The coexistence of purifying and episodic positive selection points to a balance between structural conservation and lineage-specific functional diversification.